Asesmen Standar Pembelajaran Jarak Jauh Universitas Berdasarkan ISO 29994:2021 - Santosa, Iqbal; Nurtrisha, Widyatasya Agustika (MULTINETICS, 2023)
The ISO standard 29994:2021 provides requirements for Distance Learning (PJJ) services that are not yet covered in ISO 29993:2017 which focus on learning services outside of formal education. PJJ at Telkom University has been implemented in the Informatics Distance Education Undergraduate Study Program since 2019, with the Technical Implementation Unit (UPT), namely the Postgraduate and Advanced Learning (PSAL) Directorate. This Study Program has not implemented any standards including ISO 29994:2021 in its learning services. Using the five phases of COBIT 2019 Implementation, an overview of the current conditions of the implementation of PJJ management, the gaps with the requirements of ISO 29994:2021 and recommendations for improvement are obtained. The result was that there were 4 clauses in ISO 29994:2021 which had not been fully met by Distance Learning Service Providers and were given recommendations for 18 points of improvement, namely 8 aspects of people, 4 aspects of process, and 6 aspects of technology. This recommendation is expected to be a reference for improving PJJ services at Telkom University and other Distance Learning Service Providers so they can compete internationally according to ISO 29994:2021 standards.